The equation of brain death with legal death in Islamic law: a critical appraisal - Haneef, Sayed Sikandar Shah; Abdul Razak, Mohd Abbas (University of Chitral -Pakistan, 2018)
Brain death as the modern medical criterion of death while a welcoming development for the twin purposes of saving medical cost and serving the demand for organ procurement is still a controversial subject in the field of Bioethics. The reason is that its scientific credibility in terms of conclusiveness of the termination of life of the whole body system is far from settled. Similarly, its compatibility with Islamic notion of death and its unique metaphysical criterion of the separation of the soul from human body is a debatable topic among the Muslim legists. In the Muslim debate what concerns us is the question of equating brain death to legal death. The most central issue during the juristic discourse was as to whether brain death is a definitive indicator that the soul has left the body. The answer was divergent but with minimum discourse on both theological and scientific dimensions of the issue. Accordingly, this paper argues that interrogating the issue from scientific dimension would have resulted in a more informed verdict on the issue.